PERAN KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALITAS GURU DI MA MIFTAHUL ULUM KEC. GONDANG KAB. MOJOKERTO - Umi Rosidah; Abdul Jalil; Moh Muslim (VICRATINA, 2020)
The head of madrasa supervisor has a role to coordinate and guide the teachers to be able to improve their professionalism as educators. The purpose of this study is  find out: madrasah head’s programs, strategies, and obstacles in improving teacher professionalism. This research uses a qualitative approach. Data collection techniques are done by observations, interviews, and documentations. The subject of the study were the head of the madrasa and the teachers. The results showed that. Planning a program in improving teachers professionalism prepared by the madrasah’s head and documented, which includes the RKM, RKAM, RKTM and the work program of the madrasah’s head. Madrasah’s haad as supervisor continues to carry out supervision teacher competency improvement activities, conduct services and add facilities, increase teachers discipline. Implementation of supervision in improving teachers professionalism, the activities carried out include classroom supervision, supervision of learning tools, training and workshops. Provision of supporting facilities for learning. Controlling the presence of teachers, controlling the hours of learning, and discipline of dressing. Evaluation of the madrasah’s head in improving the professionalism of teachers in MA Miftahul Ulum is the final result of the research with interviews, observations, and documentations that have been done.